1999
DOI: 10.1103/physrevlett.82.2390
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Magnetism and Magnetic Anisotropy Probed with Ferromagnetic Resonance

Abstract: Via ferromagnetic resonance both the magnetic anisotropy energy (MAE) and the spectroscopic splitting tensor (g tensor) for a bcc Fe 2 ͞V 5 ͑001͒ superlattice are measured independently. The theoretically proposed proportionality between the anisotropy of the orbital moment m L and the MAE is quantitatively checked and its limitations are discussed. From layer-resolved first-principles calculations we find a reduced spin moment m S 1.62m B for Fe and m V S 20.67m B in the first V layer. The g-tensor elements r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 22 publications
6
78
0
Order By: Relevance
“…A more detailed analysis of the behaviour below T C as it was done for FM thin films in Refs. [13] and [14] does not lead to reasonable results for CeRuPO. The huge linewidth and the metallic lineshape prevents a sufficent accuracy for the determination of the resonance field.…”
Section: Resultsmentioning
confidence: 99%
“…A more detailed analysis of the behaviour below T C as it was done for FM thin films in Refs. [13] and [14] does not lead to reasonable results for CeRuPO. The huge linewidth and the metallic lineshape prevents a sufficent accuracy for the determination of the resonance field.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, extensive work [10][11][12][13][14][15][16][17][18][19] on magnetic surfaces and thin films has shown that a lowering of the symmetry results in an increase of m L compared to bulk systems, where the d-state hybridization and the crystal field effectively quench m L . This effect gives rise to a variety of interesting phenomena, such as enhanced and perpendicular magnetic anisotropy [2,[12][13][14][15][16]19].…”
Section: Introductionmentioning
confidence: 99%
“…This effect gives rise to a variety of interesting phenomena, such as enhanced and perpendicular magnetic anisotropy [2,[12][13][14][15][16]19]. Surface-supported nanoparticles offer additional degrees of freedom to tune the magnetic anisotropy by ad-hoc modifications of the particle size, shape, and coupling with the substrate, making nanometer sized systems attractive for basic investigations as well as for miniaturized data storage applications [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] One means of determining the SOC in ferromagnets is to measure the contribution of orbital magnetization to the total moment. In the absence of SOC, the orbital moment is quenched for any crystal structure with cubic symmetry.…”
Section: Introductionmentioning
confidence: 99%